Time's enchantment & other reflections - Kilates, Marne (Ateneo de Naga University Press, 2014)
"Time's Enchantment & Other Reflections is award-winning poet Marne Kilates's new collection ranging over old and new themes of his idyllic childhood in the province and the nightmare of his hometown catching up with the urban mayhem of his adult life."--Back cover.